Social and legal guarantees of the rights of convicts according to the legislation of the Russian Federation - Mustafina, Lyaysan Renatovna; Khamitova, Gulnara Mullanurovna; Nafikova, Gulnara Ildarovna (Cuestiones Políticas, 2020)
The objective of the article is to examine the social and legal guarantees of the rights of convicts under the legislation of the Russian Federation.  The socio-documentary method was used. The square of the subject lies in the development of a system of social protection of the population in prison institutions. After all, convicts, like other people, need social protection and social security from the state. Upon entering the prisons, they experience adaptation and have no idea of the existence of certain legal and legal social guarantees. Supporting a segment of the population as convicted requires social and legal guarantees, thus improving the conditions of their service in places of deprivation of liberty. Places of deprivation of liberty are counted, because social work aimed at supporting these categories of population, such as the elderly and mothers, adheres to places of deprivation of liberty, because social work is oriented precisely to these categories of population, where necessary, as well as to protect motherhood, fatherhood and children and , inmates, have much to contribute in these areas and social segments if they meet.